DYNAMICS OF MORPHOLOGICAL INDICATORS IN THE PHYSICAL DEVELOPMENT OF LONG-DISTANCE RUNNING - Sultonov Usmon Ibragimovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The dynamics of morphological indicators of physical development of long-distance runners, effective means of training young runners at different stages of the annual cycle, quantitative indicators of physical development have been studied.